2012
DOI: 10.1128/iai.00103-12
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Meningococcal Factor H Binding Protein Mutant Vaccines That Do Not Bind Human Complement Factor H

Abstract: Meningococcal factor H binding protein (fHbp) is a human species-specific ligand for the complement regulator, factor H (fH). In recent studies, fHbp vaccines in which arginine at position 41 was replaced by serine (R41S) had impaired fH binding. The mutant vaccines elicited bactericidal responses in human fH transgenic mice superior to those elicited by control fHbp vaccines that bound human fH. Based on sequence similarity, fHbp has been classified into three variant groups. Here we report that although R41 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…To identify residues that are necessary for high affinity fH interactions, we performed extensive Ala substitution mutagenesis to produce a catalogue of amino acids in each variant family that contribute to binding to fH, and could be modified in vaccine design. This adds to the three residues already described for V1 fHbp and for V2 fHbp which are required for high affinity binding, although the affinity of the modified V2 proteins for fH was not reported [23]. Our findings illustrate differences in the precise mechanisms by which fH engages fHbp from different families, even though the same face of fHbp is involved.…”
Section: Discussionsupporting
confidence: 46%
“…To identify residues that are necessary for high affinity fH interactions, we performed extensive Ala substitution mutagenesis to produce a catalogue of amino acids in each variant family that contribute to binding to fH, and could be modified in vaccine design. This adds to the three residues already described for V1 fHbp and for V2 fHbp which are required for high affinity binding, although the affinity of the modified V2 proteins for fH was not reported [23]. Our findings illustrate differences in the precise mechanisms by which fH engages fHbp from different families, even though the same face of fHbp is involved.…”
Section: Discussionsupporting
confidence: 46%
“…The numbering of the positions of amino acid residues is based on the mature protein sequence beginning with the lipidated cysteine residue of fHbp ID 1 to facilitate comparison with our previous data [12, 16]. In our previous study of sub-family A mutants the most promising antigens appeared to be D211A and T221A/H223A 1 [16]. We subsequently found that the single amino acid substitution T221A gave an equivalent decrease in fH binding as the double mutant (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore the T221A and D211A mutant vaccines were investigated in the present study. Preparation of the D211A mutant was previously described [16]. The desired nucleotide substitutions for the T221A mutant were introduced into the pET21-fHbp ID 22 expression plasmid using the Phusion site-specific mutagenesis kit (Thermo Scientific) and the oligonucleotides: T221A_fwd, gcttaccacctcgcccttttcg; T221A_rev, gcctttttcttcgccgcc; (changes from the wild-type sequences underlined).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations